FluoMALDI Microscopy: Matrix Co‐Crystallization Simultaneously Enhances Fluorescence and MALDI Imaging - Ethan Yang; Xinyi Elaine Shen; Hoku West‐Foyle; Tae‐Hun Hahm; Maxime A. Siegler; Dalton R. Brown; Cole C. Johnson; Jeong Hee Kim; LaToya Ann Roker; Caitlin M. Tressler; Ishan Barman; Scot C. Kuo; et al. (Advanced Science, 2023)
Abstract Here, the authors report that co‐crystallization of fluorophores with matrix‐assisted laser desorption/ionization (MALDI) imaging matrices significantly enhances fluorophore brightness up to 79‐fold, enabling the amplification of innate tissue autofluorescence. This discovery facilitates FluoMALDI, the imaging of the same biological sample by both fluorescence microscopy and MALDI imaging. The approach combines the high spatial resolution and specific labeling capabilities of fluorescence microscopy with the inherently multiplexed, versatile imaging capabilities of MALDI imaging. This new paradigm simplifies registration by avoiding physical changes between fluorescence and MALDI imaging, allowing to image the exact same cells in tissues with both modalities. Matrix‐fluorophore co‐crystallization also facilitates applications with insufficient fluorescence brightness. The authors demonstrate  feasibility of FluoMALDI imaging with endogenous and exogenous fluorophores and autofluorescence‐based FluoMALDI of brain and kidney tissue sections. FluoMALDI will advance structural‐functional microscopic imaging in cell biology, biomedicine, and pathology.